1996
DOI: 10.1002/(sici)1096-8628(19960809)64:2<241::aid-ajmg1>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic mouse model for the fragile X syndrome

Abstract: Transgenic fragile X knockout mice have been constructed to provide an animal model to study the physiologic function of the fragile X gene (FMR1) and to gain more insight into the clinical phenotype caused by the absence of the fragile X protein. Initial experiments suggested that the knockout mice show macroorchidism and cognitive and behavioral deficits, abnormalities comparable to those of human fragile X patients. In the present study, we have extended our experiments, and conclude that the Fmr1 knockout … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
89
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 162 publications
(89 citation statements)
references
References 17 publications
0
89
0
Order By: Relevance
“…As in humans, Fmr1 knockout mice have macroorchidism, which is evident from PND 15 onwards and results in an increase of testicular weight by 30% after 6 months (Bakker et al, 1994;Kooy et al, 1996;Kooy et al, 1998). Dendritic spine abnormalities are a hallmark of FXS patients (Hinton et al, 1991) and this is recapitulated in Fmr1 knockout mice.…”
Section: The Mouse Model and Molecular Mechanisms Of Fragile X Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…As in humans, Fmr1 knockout mice have macroorchidism, which is evident from PND 15 onwards and results in an increase of testicular weight by 30% after 6 months (Bakker et al, 1994;Kooy et al, 1996;Kooy et al, 1998). Dendritic spine abnormalities are a hallmark of FXS patients (Hinton et al, 1991) and this is recapitulated in Fmr1 knockout mice.…”
Section: The Mouse Model and Molecular Mechanisms Of Fragile X Syndromementioning
confidence: 99%
“…Seizure incidence in knockout mice have been shown peak in the third week of postnatal life (Yan et al, 2005). Finally, several independent studies have shown knockout mice to be hyperactive in the open field test (Bakker et al, 1994;Kooy et al, 1996;Mineur et al, 2002).…”
Section: The Mouse Model and Molecular Mechanisms Of Fragile X Syndromementioning
confidence: 99%
“…48 The Fmrp (fragile X mental retardation protein)-deficient mouse, a model for FXS, exhibits marked susceptibility to audiogenic seizures [49][50][51] and evidences the enlarged testes, although not the facial dysmorphology, characteristic of the human disease. [51][52][53][54] Most studies report that the loss of Fmrp in mice does not lead to overt motor impairment, severe learning deficiencies, or a lack of social approach. Alterations in the behavioral phenotype of the Fmr1-null mouse include increased levels of social anxiety, 55 reduced social interaction, 56 hyperactivity, 52,57-60 and deficits in spatial learning on a radial arm maze 57 and reversal learning in the Morris water maze task 52,53,61 (see also Ref.…”
Section: Mouse Models Of Genetic Clinical Disorders With Autism Symptmentioning
confidence: 99%
“…[51][52][53][54] Most studies report that the loss of Fmrp in mice does not lead to overt motor impairment, severe learning deficiencies, or a lack of social approach. Alterations in the behavioral phenotype of the Fmr1-null mouse include increased levels of social anxiety, 55 reduced social interaction, 56 hyperactivity, 52,57-60 and deficits in spatial learning on a radial arm maze 57 and reversal learning in the Morris water maze task 52,53,61 (see also Ref. 62).…”
Section: Mouse Models Of Genetic Clinical Disorders With Autism Symptmentioning
confidence: 99%
“…An excess of dendritic spines in fragile X patients indicates a deficit in synaptic pruning. This pathology is also seen in mice that are deficient in FMRP whose pyramidal neurons show an excess of spines [Kooy et al, 1996]. Other forms of mental retardation seem to implicate synaptogenesis as a key step in cognitive development.…”
Section: Suggestive Evidence Linking Disruptions In Synaptogenesis Wimentioning
confidence: 95%